Management of Student Entrepreneurship Education at Darussalam Gontor Modern Islamic Boarding School, Ponorogo - Arsandi Arsandi; Amaliah Farhan; Munirul Abidin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
Entrepreneurship management has a broad meaning, this aricle focuses on the management of entrepreneurship education in the modern cottage of Darussalam Gontor. Pondok medoren Darussalam Gontor has various fields of business to advance education and is able to educate the students to be able to be responsible and able to carry out a mandate given by the cottage, both senior students and their teachers. Entrepreneurship in darussalam Gontor modren cottage can be seen from the books learned in the classroom and outside the classroom, there is also entrepreneurship in the form of activities that will stimulate one's interest in studying in the modern cottage Darusslam gontor. This article is written with literature research or library research and case studies, which are from aricles, documents, and journals related to the research carried out.